Creative, Yet Practical: 20 Years of Distance Education Teacher Preparation. (December 2019) - Jordan, LuAnn; Spooner, Fred; Anderson, Kelly; Dillon, Ann S.
For more than 20 years, distance education has provided an option for prospective special education teachers to achieve licensure and a graduate degree. The program began as a two-way interactive television endeavor located at area community college sites. Over time, the program evolved to include online coursework with synchronous class meetings. In addition, changes in licensure and the graduate program have affected the schedule and offerings. Although changes are part of the story, the mission has remained the same, to provide quality graduate instruction to teachers of students with disabilities in a convenient, connected manner. This article includes a reflection on the original program and highlights of four major transitions over the 20 years of the program.